[Translated article] SCIWORA in children. A rare clinical entity: Ambispective study - L.M. Romero-Muñoz; M. Peral-Alarma; A. Barriga-Martín (Revista Española de Cirugía Ortopédica y Traumatología, 2024)
Introduction: SCIWORA has a low incidence but a high functional repercussion. The aim of the present study was to characterize the epidemiology of this clinical–radiological condition and evaluate functional outcome with a mean of 10-years follow-up. Material and methods: Observational, longitudinal ambispective cohort study. Thirteen SCIWORA patients were admitted in the study period. Demographics, mechanism of injury, spinal cord MRI findings, neurological level of injury, time to SCI, neurological status (AIS) at admission/discharge/5 years, spinal cord independence measure (SCIM III) scale at admission and discharge, hospital length of stay and mean follow-up were recorded. On October 2022 patients were re-evaluated using NDI, Oswestry, and SV-QLI/SCI. Results: Median age was 4 years. The study population for this investigation was mostly men (77%). 54% of level of injury correspond to cervical spine. AIS at admission was A (31%) and C (31%). Neurological level of injury was C2 (22%) and T10 (15%). Motor vehicle-related injury was the most prevalent mechanism of injury (77%), SCIM III scale at admission and discharge: 28.5/42, hospital length of stay was 115 days. The NDI was 11.6, Oswestry: 15.3 and SV-QLI/SCI: 17. Conclusions: Seventy-seven percent of SCIWORA patients was detected under 8 years-old. At 1 year follow-up after discharge 31% patients were AIS grade D and with 5 years follow-up the percentage remain constant. No statistically significant differences in the mechanism of injury and MRI findings (P = 0.872), age and MRI spinal cord findings (P = 0.149) were found in SCIWORA patients. Resumen: Introducción: La lesión medular tipo SCIWORA es una entidad clínica con baja incidencia y alta repercusión funcional. El objetivo del estudio es la descripción epidemiológica de esta lesión y su evolución funcional con un seguimiento medio de 10 años. Material y métodos: Estudio analítico, longitudinal, de cohortes ambispectivo. Fueron evaluados 13 pacientes con el diagnóstico de SCIWORA en el periodo de estudio 2001-2022. Variables evaluadas: edad, sexo, días hasta la lesión medular, causa de la lesión, imagen medular en la RM postraumatismo, nivel neurológico de la lesión, ASIA ingreso/alta/5 años, SCIM III ingreso/alta/3 años, tipo de tratamiento empleado, empleo de terapia NASCIS III ingreso, tiempo de hospitalización, seguimiento medio. En octubre de 2022 fueron nuevamente evaluados en consultas externas mediante: cuestionario de discapacidad cervical (NDI)/Oswestry y cuestionario de calidad de vida validado en castellano para lesionados medulares (SV-QLI/SCI). Resultados: La mediana de edad fue de 4 años, 77% varones. El 54% de las lesiones corresponden a nivel cervical. El ASIA al ingreso fue del 31% A y del 31% C, nivel neurológico: C2 (22%) y T10 (15%), tráfico como causa de lesión (77%), SCIM III ingreso/alta: 28,5/42. La estancia media hospitalaria fue de 115 días. NDI: 11,6 y Oswestry: 15,3. Conclusión: El 77% de los SCIWORA se producen en menores de 8 años. Al año del alta hospitalaria el 31% de los pacientes fueron catalogados como ASIA D y a los 5 años el porcentaje se mantiene constante. No se encontraron diferencias significativas entre la causa de la lesión y el tipo de alteración en RM (p = 0,872), ni entre la edad y el tipo de lesión medular objetivada en RM (p = 0,149).